Safety, efficacy, and maneuverability of a self-propelled capsule endoscope for observation of the human gastrointestinal tract - Ota, Kazuhiro; Kojima, Yuichi; Kakimoto, Kazuki; Nouda, Sadaharu; Takeuchi, Toshihisa; Shindo, Yasunori; Ohtsuka, Yoshitake; Ohtsuka, Naotake; Higuchi, Kazuhide (Endoscopy International Open, 2021)
Background and study aims We developed a self-propelled capsule endoscope that can be controlled from outside the body with real-time observation. To improve the device, we conducted a clinical trial of total gastrointestinal capsule endoscopy in healthy subjects to ascertain whether our first-generation, self-propelled capsule endoscope was safe and effective for observing the entire human gastrointestinal tract.Patients and methods After adequate gastrointestinal pretreatment, five healthy subjects were instructed to swallow a self-propelling capsule endoscope and the safety of a complete gastrointestinal capsule endoscopy with this device was assessed. We also investigated basic problems associated with complete gastrointestinal capsule endoscopy.Results No adverse effects of the magnetic field were identified in any of the subjects. No mucosal damage was noted in any of the subjects with the use of our first-generation, self-propelling capsule endoscope. We found that it took longer than expected to observe the stomach; the view was compromised by the swallowed saliva. The pylorus was extremely difficult to navigate, and the endoscope’s fin sometimes got caught in the folds of the small intestine and colon.Conclusions To resolve the problems associated with the existing self-propelling capsule endoscope, it may be necessary to not only improve the capsule endoscopes, but also to control the environment within the gastrointestinal tract with medications and other means. Our results could guide other researchers in developing capsule endoscopes controllable from outside the body, thus allowing real-time observation.